(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the frequency of hyperhomocysteinaemia in ischemic stroke patients and its association with other risk factors. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the department of general medicine Nishtar Hospital, Multan, from November 2020 to November 2021 for a period of one-year, Materials and Methods: A total of 120 patients were enrolled from outpatients and emergency department of hospital. After clinical examination and 8 hours fasting venous blood sample was taken aseptically for ethylene diamine tetra acetate analysis. Main variables of study were age, gender, diabetes, hypertension and homocysteine level. SPSS version 23 was used for data analysis. Mean and SD was calculated for numerical data and frequency percentages for categorical data. Results: Majority of the patients were (68.3%) between age group 40-60 years. Hypertension and diabetes mellitus was observed as (47.5%) and (31.7%), respectively. Among total 67.5% patients had hyperhomocysteinaemia, >15mmol/L. It was seen that the differences were not statistically significant. Conclusion: Hyperhomocysteinaemia is a strong risk factor that is responsible for number of ischemic stroke incidents in Pakistani population. Preventive measures of hyperhomocysteinaemia will lessen the incidence of ischemic stroke.